Desistance research and critical criminology: a conversation = Desistance-Forschung und Kritische Kriminologie : eine Konversation - Graebsch, Christine; Maruna, Shadd (Kriminologisches Journal, 2022)
Critical criminologists in Germany have been criticized for dealing with desistance research. In the opinion of Peters (in this volume) both perspectives of research are outright incompatible with each other. This critique is based on a certain understanding of the labeling approach that is prevalent in German-language critical criminology. From this perspective, crime is understood exclusively as an attribution. Desistance research is then perceived as a backlash towards an etiological understanding of crime. Peters addresses his critique especially towards the reception of Maruna’s work that in Peters’ eyes takes crime for "real" (as of a behavioral quality) and supports the hegemonial normative system. As opposed to this, critical criminology and desistance research seem to coexist quite peacefully in international criminology - with Maruna being one of the most prominent proponents of their combination. However, their relation to each other is usually not analysed and discussed. Therefore, Christine Graebsch asked Shadd Maruna for his respective contribution. It resulted in the following conversation.